Cardiovascular outcomes following a respiratory tract infection among adults with non-CF bronchiectasis: a general population based study - Navaratnam, Vidya; Root, Adrian A; Douglas, Ian; Smeeth, Liam; Hubbard, Richard B.; Quint, Jennifer K. (American Thoracic Society, 2018)
Rationale: Studies suggest that people with bronchiectasis are at increased risk of cardiovascular co-morbidities.